When jump height is not a good indicator of lower limb maximal power output: Theoretical demonstration, experimental evidence and practical solutions - Morin, J.-B.; Jiménez-Reyes, P.; Brughelli, M.; Samozino, P. (Sports Medicine, 2019)
Lower limb external maximal power output capacity is a key physical component of performance in many sports. During squat jump and countermovement jump tests, athletes produce high amounts of mechanical work over a short duration to displace their body mass (i.e. the dimension of mechanical power). Thus, jump height has been frequently used by the sports science and medicine communities as an indicator of the power output produced during the jump and by extension, of maximal power output capacity. However, in this article, we contend that squat jump and countermovement jump height are not systematically good indicators of power output produced during the jump and maximal power output capacity. To support our opinion, we first detail why, theoretically, jump height and maximal power output capacity are not fully related. Specifically, we demonstrate that individual body mass, push-off distance, optimal loading and the force-velocity profile confound the jump height-power relationship. We also discuss the relationship between squat jump or countermovement jump height and maximal power output capacity measured with a force plate based on data reported in the literature, which added to our own experimental evidence. Finally, we discuss the limitations of existing practical solutions (regression-based estimation equations and allometric scaling), and advocate using a valid, reliable and simple field-based procedure to compute individual power output produced during the jump and maximal power output capacity directly from jump height, body mass and push-off distance. The latter may allow researchers and practitioners to reduce bias in their assessment of lower limb mechanical power output by using jump height as an input with a simple yet accurate computation method, and not as the first/only variable of interest.